A modified inherent strain model with consideration of the variance of mechanical properties in metal additive manufacturing. (December 2021) - Wang, Yanfei; Li, Quan; Qian, Lingyun; Yang, Yabin
Abstract: Residual stresses and deformations are one of the main challenges for metal additive manufacturing (AM). The multiscale nature of the metal AM poses certain difficulties for conventional melt pool tracking models to predict the residual stresses and deformations within a reasonable amount of time, thus causing obstacles for further process optimization. The inherent strain method, which incorporates the influence of the process history into the inherent strain and calculates the final stress-strain state in a single mechanical step, is a promising approach to solve the above problems. In the present study, based on a modified inherent strain (MIS) method which is specifically developed for AM, a strategy for considering the variance of the mechanical properties during the AM process (termed as MIS-VM) is proposed. The accuracy of the proposed MIS-VM model is compared with an experiment conducted in literature and a detailed thermo-mechanical model for various process parameters and heat source moving paths. The results show that the mechanical properties are essential for accurate predictions of the stresses and deformations in the MIS method. Compared to the MIS model with constant properties, the accuracy of the MIS-VM model can be improved as large as 10%. The high computational efficiency of the proposed model also suggests it is promising to be incorporated in an optimization method for the topology or process parameters.